2019
DOI: 10.1039/c9gc00064j
|View full text |Cite
|
Sign up to set email alerts
|

Direct construction of carbazoles from 2-methyl-indole-3-carbaldehydes and enals

Abstract: The direct and rapid construction of carbazoles was achieved based on the reaction of 2-methyl-indole-3-carbaldehydes and enals promoted by the Lewis acid LiCl and DBU in a single operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…[4+2] annulation has proven as one of the most powerful and reliable strategies for the construction of structurally diverse six‐membered rings from simple raw materials . Recently, we have developed the direct and rapid construction of carbazoles via oxidative [4+2] annulation of 2‐methyl‐indole‐3‐carbaldehydes with enals promoted by LiCl/DBU in a single operation . As part of our ongoing interest in the synthesis of carbo‐ and heterocycles, we envisaged a novel strategy for the synthesis of highly functionalized indolizines might be achieved via oxidative [4+2] annulation of 1‐acetylaryl 2‐formylpyrroles and enals.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…[4+2] annulation has proven as one of the most powerful and reliable strategies for the construction of structurally diverse six‐membered rings from simple raw materials . Recently, we have developed the direct and rapid construction of carbazoles via oxidative [4+2] annulation of 2‐methyl‐indole‐3‐carbaldehydes with enals promoted by LiCl/DBU in a single operation . As part of our ongoing interest in the synthesis of carbo‐ and heterocycles, we envisaged a novel strategy for the synthesis of highly functionalized indolizines might be achieved via oxidative [4+2] annulation of 1‐acetylaryl 2‐formylpyrroles and enals.…”
Section: Methodsmentioning
confidence: 99%
“…[12] As part of our ongoing interest in the synthesis of carbo-and heterocycles, [13] we envisaged an ovel strategy for the synthesis of highly functionalized indolizines might be achieved via oxidative [4+ +2] annulation of 1-acetylaryl 2-formylpyrroles and enals. Solventc oncentration investigation indicated that 2.0 mL is proper, generating 5, 6-dihydroindolizine 3a in up to 89 %y ield with 17:1 dr (entries [12][13][14][15]. Notably,Z ou group reported "one-pot" multicomponent methodt oi ndolizines and pyrido[1,2-a]indoles via pyridine-ring construction.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, carbazole derivatives also have potential applications in optoelectronic materials, conducting polymers, and synthetic dyes [9][10][11]. Over the past decades, many efficient synthetic methodologies for functionalized carbazole derivatives have been successfully developed [12][13][14][15][16][17][18]. Because indoles are readily available materials, the direct extension of indoles to carbazole skeletons has a great advantage [19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%